TDNAscan: A Software to Identify Complete and Truncated T-DNA Insertions - Sun, Liang; Ge, Yinbing; Sparks, J. Alan; Robinson, Zachary T.; Cheng, Xiaofei; Wen, Jiangqi; Blancaflor, Elison B. (Frontiers in Genetics, 2019)
Transfer (T)-DNA insertions in mutants isolated from forward genetic screens are typically identified through thermal asymmetric interlaced polymerase chain reaction (TAIL-PCR), inverse PCR or plasmid rescue. Despite the popularity and success of these methods, they have limited capabilities, particularly in situations in which the T-DNA is truncated. Here, we present a next generation sequencing (NGS)-based platform to facilitate the identification of complete and truncated T-DNA insertions. Our method enables the detection of the corresponding T-DNA insertion orientation and zygosity, as well as insertion annotation. This method called TDNAscan was developed to be an open source software. We expect that TDNAscan will be a valuable addition to forward genetics toolkits because it provides a solution to the problem of causal gene identification, particularly genes disrupted by truncated T-DNA insertions. We present a case study in which TDNAscan was used to determine that the recessive Arabidopsis thaliana hypersensitive to latrunculin B (hlb3) mutant isolated in a forward genetic screen of T-DNA mutagenized plants, encodes a class II FORMIN.